Effect of Cation Composition on the Mechanical Stability of Perovskite Solar Cells. Issue 9 (4th December 2017) - Rolston, Nicholas; Printz, Adam D.; Tracy, Jared M.; Weerasinghe, Hasitha C.; Vak, Doojin; Haur, Lew Jia; Priyadarshi, Anish; Mathews, Nripan; Slotcavage, Daniel J.; McGehee, Michael D.; Kalan, Roghi E.; Zielinski, Kenneth; et al.
Abstract: Photoactive perovskite semiconductors are highly tunable, with numerous inorganic and organic cations readily incorporated to modify optoelectronic properties. However, despite the importance of device reliability and long service lifetimes, the effects of various cations on the mechanical properties of perovskites are largely overlooked. In this study, the cohesion energy of perovskites containing various cation combinations of methylammonium, formamidinium, cesium, butylammonium, and 5‐aminovaleric acid is reported. A trade‐off is observed between the mechanical integrity and the efficiency of perovskite devices. High efficiency devices exhibit decreased cohesion, which is attributed to reduced grain sizes with the inclusion of additional cations and PbI2 additives. Microindentation hardness testing is performed to estimate the fracture toughness of single‐crystal perovskite, and the results indicated perovskites are inherently fragile, even in the absence of grain boundaries and defects. The devices found to have the highest fracture energies are perovskites infiltrated into a porous TiO2 /ZrO2 /C triple layer, which provide extrinsic reinforcement and shielding for enhanced mechanical and chemical stability. Abstract : As reflected in the fragility of state‐of‐the‐art perovskite solar cells, mechanical reliability has too long been an afterthought in their development. The aim of this work is to understand the effects of cation composition (combinations of methylammonium, formamidinium, cesium, butylammonium, and 5‐aminovaleric acid) on perovskite mechanical integrity and determine design criteria to increase reliability toward the development of module‐scale devices.